Elucidating the neurodegnerative sequelae leading to VCID pathology. (December 2021) - Early, Alexandria N; Weekman, Erica M; Sudduth, Tiffany L; Price, Brittani R; Woolums, Abigail E; Hawthorne, Danielle; Seaks, Charles E; Wilcock, Donna M
Abstract: Background: Vascular contributions to cognitive impairment and dementia (VCID) are one of the leading causes of dementia. High levels of plasma homocysteine or hyperhomocysteinemia has been characterized as a risk factor for VCID however, the mechanism underlying this connection remains elusive. I hypothesize that hyperhomocysteinemia initiates a pro‐inflammatory cascade that increases the activity of matrix metalloproteinase 9 (MMP9) causing perivascular astrocytes to dissociate from their vessels, leading to blood brain barrier dysfunction and the progression toward VCID pathology. Method: For in vivo studies, C57BL6 WT mice were placed on a control diet or a diet deficient in folate, vitamins B6 and B12 and enriched in methionine to induce hyperhomocysteinemia for 6, 10, 14, or 18 weeks. Immunohistochemistry and gene expression analysis were used to determine neuroinflammatory changes while histology was used to identify changes in astrocytic end‐feet proteins and microhemorrhages. Gel zymography was used to assess proteinase activity of MMP9. Behavior was assessed using the 2‐day radial arm water maze. For in vitro, experiments, primary astrocytes obtained from both WT and MMP9 null mice were placed in a co‐culture model with WT primary endothelial cells. Trans‐endothelial electrical resistance measurements were used to assess blood brain barrier integrity in response to homocysteine in vitro . Result: After 6 weeks of diet administration, we saw a significant increase in gene expression of TNFα, IL‐1β, IL‐6 and IL‐12α. This was followed by increases in MMP transcription and proteinase activity seen at 10 weeks on diet. Also, beginning at the 10‐week time point, cognitive deficits became detectable, which coincided with significant disruptions between astrocytic end‐feet and the cerebrovasculature. Finally, there was a significant increase in the number of microhemorrhages after 14 weeks on diet. In vitro, astrocytes showed an increase in MMP9 after 48 hours of homocysteine treatment. Conclusion: Collectively, our findings suggest that astrocytic MMP9 may play an integral role in the mechanism associating homocysteine induced neuroinflammation with vascular pathogenesis leading to VCID. Continued study of the cell specificity and mechanism of MMP9 mediated vascular pathology will allow us to systematically target the various stages of disease and ultimately prevent the progression of VCID.